(untitled) (Historia, 2021)
I have been asked to set the ball rolling as it were, i.e. to givea general introduction to the more topical papers which are to follow.What I have to offer is no more than a few brief, if not perfunctory,remarks on the general problem of reinterpretation in history.There is no need to remind you that the term "history" has at leastthree meanings, two of which are germane to our discussion this morning.History can either denote the actual course of events in the past, or itcan signify the historian’s account of those events. Clearly I have twodistinct things in mind when I speak of the history of South Africa andwhen I speak of Walker’s History of South Africa. The one refers tothe actual events, the other to Walker’s account of them. Authoritativehistory (in the second sence) is history which accords most closely tothe actual past. But the connection between the two is, I fear, often tenuous,if not non-existent. Yet there can be no "true" history because we cannever know whether it is true. True history is a contradiction in terms.It is easy enough to say that the Great Trek occurred (and even that termis, significantly enough, of much later date), it is impossible to say whythe Great Trek happened